2017
DOI: 10.1080/10286020.2017.1384819
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of gallic acid on gentamicin-induced nephrotoxicity in rats

Abstract: The major side effect of gentamicin (GEN) is nephrotoxicity which in turn restricts the clinical use of this drug. In this study, the effect of gallic acid (GA) on gentamicin-induced nephrotoxicity was studied. A total number of 28 male Wistar rats were randomly divided into four experimental groups: control, GEN (100 mg/kg/day), GEN + GA (30 mg/kg/day), GA (30 mg/kg/day). All drug administrations were done intraperitoneally (i.p) for eight consecutive days. Twenty-four hours after the last administration, blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
34
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 24 publications
9
34
0
1
Order By: Relevance
“…Marino et al [53] reported GA scavenging efficiency as compared to melatonin, sesamol, protocatechuic acid and capsaicin. In accordance with our results, Reckziegel et al [54] and Ghaznavi, et al [55] confirmed GA-induced elevated levels of SOD and CAT, which reported substantial improvement after GA treatment. The observable amelioration of AOH-induced inflammatory cellular infiltrations in GA group suggests its anti-inflammatory properties.…”
Section: Discussionsupporting
confidence: 93%
“…Marino et al [53] reported GA scavenging efficiency as compared to melatonin, sesamol, protocatechuic acid and capsaicin. In accordance with our results, Reckziegel et al [54] and Ghaznavi, et al [55] confirmed GA-induced elevated levels of SOD and CAT, which reported substantial improvement after GA treatment. The observable amelioration of AOH-induced inflammatory cellular infiltrations in GA group suggests its anti-inflammatory properties.…”
Section: Discussionsupporting
confidence: 93%
“…Gentamicin-induced nephrotoxicity at the beginning of the development of the pathological process is characterized by the development of oliguric form of renal failure, accompanied by retention azotemia, proteinuria, increased loss of sodium and potassium ions with urine, resulting in hypokalemia (Table 1), which reflects the significant damage and death of proximal tubular cells along with injury of glomeruli, and corresponds to the results of similar experimental studies of other authors [1, 4, 8-12, 17, 18]. According to the obtained results of the morphological examination, histopathological changes, namely the necrosis and degeneration of the proximal tubular epithelial cells in the form of vacuolization and hydropic dystrophy, and glomerular damage ( Figure 2) were revealed for gentamicin nephropathy [3,[8][9][10][11][12]14]. It is known that the most important mechanism of gentamicin nephrotoxicity is the hyperproduction of reactive oxygen species, causing damage to proteins, DNA and peroxidation of lipids, with an alteration of the integrity of cellular membranes and development of morphofunctional disorders [1,17].…”
Section: Discussionsupporting
confidence: 88%
“…It is known that the most important mechanism of gentamicin nephrotoxicity is the hyperproduction of reactive oxygen species, causing damage to proteins, DNA and peroxidation of lipids, with an alteration of the integrity of cellular membranes and development of morphofunctional disorders [1,17]. This fact conditions numerous research on the effectiveness of prevention of the gentamicin nephropathy, using known and new antioxidants [1,2,4,[8][9][10][11][12]20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the adverse effects of GM were significantly improved by 12 days of GA administration (100 mg/kg), showing that the nephroprotective effects of GA against GM nephrotoxicity. More recently, similar studies showed that GA in doses of 30, 200, 400 mg/kg administration for seven or eight consecutive days could improve renal histopathological lesions and kidney dysfunction in rats intoxicated with GM, likely through its antioxidant activities and its ability to maintain the cellular membrane integrity [38]. Also, previous studies indicated that GA could protect the kidney in pathological situations such as lindane induced toxicity [39,40] and RIR [19] through its anti-oxidative properties.…”
Section: Discussionmentioning
confidence: 91%